2020
DOI: 10.3390/agronomy10040605
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Pro-Smallholder Farmers’ Permanent Mulch for Better Soil Quality and Food Security Under Conservation Agriculture

Abstract: Soil degradation is the greatest threat to agricultural production globally. The practice of applying or retaining crop residues in the field as mulch is imperative to prevent soil erosion, maintain soil quality and improve crop productivity. However, smallholder farmers resort to maximizing profit by removing crop residues after harvest to sell or use them as feed for livestock. Agrimats are innovative pro-smallholder farming mulching materials that are manufactured using cheap or freely available organic was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The Benefits of CA Impacts on Soil Quality Soil is considered to be of good quality when it can sustain biological productivity, maintain environmental quality, and promote plant and animal health. The positive impact of CA with respect to soil quality improvement is often exhibited by an increase in soil organic carbon, good infiltration rates, high water-holding capacity, and good soil structure (Naab et al 2017;Bamutaze et al 2019;Mgolozeli et al 2020). For instance, in their study, Mgolozeli et al (2020) demonstrated the effect of CA in improving soil organic carbon particularly in the top 10-cm soil depth, promoting higher soil aggregate stability and improving the overall condition of the soil.…”
Section: Status Of Sustainable Agriculture In Kenyamentioning
confidence: 98%
See 2 more Smart Citations
“…The Benefits of CA Impacts on Soil Quality Soil is considered to be of good quality when it can sustain biological productivity, maintain environmental quality, and promote plant and animal health. The positive impact of CA with respect to soil quality improvement is often exhibited by an increase in soil organic carbon, good infiltration rates, high water-holding capacity, and good soil structure (Naab et al 2017;Bamutaze et al 2019;Mgolozeli et al 2020). For instance, in their study, Mgolozeli et al (2020) demonstrated the effect of CA in improving soil organic carbon particularly in the top 10-cm soil depth, promoting higher soil aggregate stability and improving the overall condition of the soil.…”
Section: Status Of Sustainable Agriculture In Kenyamentioning
confidence: 98%
“…The positive impact of CA with respect to soil quality improvement is often exhibited by an increase in soil organic carbon, good infiltration rates, high water-holding capacity, and good soil structure (Naab et al 2017;Bamutaze et al 2019;Mgolozeli et al 2020). For instance, in their study, Mgolozeli et al (2020) demonstrated the effect of CA in improving soil organic carbon particularly in the top 10-cm soil depth, promoting higher soil aggregate stability and improving the overall condition of the soil. Comparative studies of the infiltration capacity of soils under no-tillage (NT) and CT systems showed that soils in the NT system had higher total infiltration, and in the final steady state, the NT plots had an infiltration rate that was four times that of the CT plots (Fig.…”
Section: Status Of Sustainable Agriculture In Kenyamentioning
confidence: 98%
See 1 more Smart Citation
“…This technique has mainly been studied in vegetables [9][10][11][12][13][14][15], cereals [13,[15][16][17][18][19], some fruit species [1,4,8,20,21] and in forestry [6]. Several studies have demonstrated effects on weed control [18], fruit yield [6,[13][14][15]18], fruit weight, plant development [1], the absorption and accumulation of nutrients in plants [4,10,11], water use efficiency [4,11,[15][16][17]22], changes in soil temperatures [16,17] and cover effects on root growth [23]. However, it is also necessary to evaluate fruit quality (firmness and size) and physiological characteristics to minimize stress in the plant, influenced by the use of mulches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies were devoted to the problem of assessing soil quality in different countries (Baliuk et al. [3]; Bartolomei et al [4]; Colantoni et al [5]; Huera-Lucero et al [6]; Salvati et al [7]; Vashisht et al [8]) and innovative measures to improve (i) soil quality under different land use systems and (ii) food security under conservation agriculture (Abdul Rahman et al [9]; Fantappiè et al [10]; Mgolozeli et al [11]; Pan et al [2]). The results of studies indicate that «although the recycling of organic materials to fields is considered a key practice for improving soil quality, the effects of this procedure was found to reduce farm profitability due to increases in material costs and labour» [2].…”
mentioning
confidence: 99%